Penatalaksanaan Nyeri Punggung pada Ibu Hamil Trimester III: Tinjauan Literatur Terbaru tentang Intervensi Non-Farmakologis dan Peran Perawatan Kebidanan - Tri Restu Handayani (Journal of Educational Innovation and Public Health, 2025)
Low back pain is one of the most common complaints experienced by pregnant women, particularly in the third trimester, as a result of various physiological, hormonal, and biomechanical changes that occur during pregnancy. Changes in posture, weight gain, and shifts in the center of gravity contribute to the development of this condition. This study aims to examine various non-pharmacological interventions that can be used to reduce low back pain in pregnant women and to analyze the role of midwives in implementing these interventions in midwifery practice. The method employed is a narrative literature review synthesizing ten verified and relevant studies, particularly those discussing prenatal yoga and pregnancy exercise as forms of non-pharmacological intervention. The results indicate that the implementation of prenatal yoga and pregnancy exercise is effective in reducing the intensity of low back pain, improving muscle flexibility and strength, and providing physical and psychological relaxation for pregnant women. In addition, these interventions contribute to increased comfort and improved quality of life during pregnancy. The findings of this study support the importance of evidence-based midwifery practice and highlight the active role of midwives in providing education, assistance, and empowerment for pregnant women through the application of safe and effective non-pharmacological interventions.